On the current location of the Old Prussian “Trace of Basel” - Ardoino, Diego (Baltistica, 2012)
Codicological, palaeographic and philological observations show that the Trace of Basel is subsequent to the date generally attributed to it (1369) and identify the cause for which TB was inserted in its present location in the colophon, particularly in the talking drawing that follows it.